Particle size effect in different base fluids on the thermal conductivity of fatty acid coated magnetite nanofluids - Dadwal, Arun; Joy, P. A. (Journal of Molecular Liquids, 2020)
The effect of particle size on the thermal conductivity of nanofluids is studied by dispersing myristic acid coated magnetite (Fe3O4) nanoparticles in two different base fluids; toluene and kerosene. Magnetite nanoparticles of three different sizes 4, 7 and 10 nm dispersed in toluene and kerosene showed a linear increase in the thermal conductivity with increasing concentration of the nanopartides, above a critical concentration. The critical concentration below which the thermal conductivity remained unchanged with the concentration of the nanopartides is found to be lower for the kerosene-based fluids. The variation of thermal conductivity with particle size is without any clear trend. However, within the measurement errors (+/- 1%), the toluene-based fluids showed a decrease in the thermal conductivity with increasing particle size, whereas the opposite trend is observed for the kerosene-based fluids. Also, the kerosene-based fluids at similar concentrations of the nanopartides showed relatively larger enhancement in the thermal conductivity than the toluene-based fluids. The observed role of the base fluid in enhancing the thermal conductivity is correlated with the difference in the solvent-surfactant interactions which in turn affect the interfacial thermal resistance at the particle-fluid interface. The thermal conductivity of the nanofluids in toluene and kerosene is also found to show different trends with the size of the particles in the presence of an external magnetic field. The difference in the enhancement of thermal conductivity of the fluids in a magnetic field is explained in terms of the differences in the magnetic dipolar interactions, clustering/ agglomeration, and magnetic characteristics of the samples as well as the characteristics of the base fluid. (C) 2020 Elsevier B.V. All rights reserved.